Euclid: II. The VIS instrument - Cropper, M. S.; Al-Bahlawan, A.; Amiaux, J.; Awan, S.; Azzollini, R.; Benson, K.; Berthe, M.; Boucher, J.; Bozzo, E.; Brockley-Blatt, C.; Candini, G. P.; Cara, C.; et al. (EDP SCIENCES S A, 2025)
This paper presents the specification, design, and development of the Visible Camera (VIS) on the European Space Agency's Euclid mission. VIS is a large optical-band imager with a field of view of 0.54 deg(2) sampled at 0 ''.1 with an array of 609 Megapixels and a spatial resolution of 0 ''.18. It will be used to survey approximately 14 000 deg(2) of extragalactic sky to measure the distortion of galaxies in the redshift range z = 0.1-1.5 resulting from weak gravitational lensing, one of the two principal cosmology probes leveraged by Euclid. With photometric redshifts, the distribution of dark matter can be mapped in three dimensions, and the extent to which this has changed with look-back time can be used to constrain the nature of dark energy and theories of gravity. The entire VIS focal plane will be transmitted to provide the largest images of the Universe from space to date, specified to reach m(AB) >= 24.5 with a signal-to-noise ratio S/N >= 10 in a single broad I-E similar or equal to (r + i + z) band over a six-year survey. The particularly challenging aspects of the instrument are the control and calibration of observational biases, which lead to stringent performance requirements and calibration regimes. With its combination of spatial resolution, calibration knowledge, depth, and area covering most of the extra-Galactic sky, VIS will also provide a legacy data set for many other fields. This paper discusses the rationale behind the conception of VIS and describes the instrument design and development, before reporting the prelaunch performance derived from ground calibrations and brief results from the inorbit commissioning. VIS should reach fainter than m(AB) = 25 with S/N >= 10 for galaxies with a full width at half maximum of 0 ''. 3 in a 1 ''.3 diameter aperture over the Wide Survey, and m(AB) >= 26.4 for a Deep Survey that will cover more than 50 deg(2). The paper also describes how the instrument works with the Euclid telescope and survey, and with the science data processing, to extract the cosmological information.